Zero-temperature relaxation in spin-polarized Fermi systems - Meyerovich, A.E.; Naish, J.H.; Owers-Bradley, J.R.; Stepaniants, A. (Физика низких температур, 1997)
The effect of zero-temperature attenuation, which has been recently observed in spin dynamics of Fermi liquids, on various processes in helium and ferromagnetic systems is described. A brief review of theoretical and experimental data on zero-temperature attenuation in transverse spin dynamics of helium systems is followed by a discussion of coupling between longitudinal and transverse processes, the Castaing instability in ³He and ³He−⁴He mixtures, and applications to pure ferromagnetic metals.